In vitro modification of cisplatin cytotoxicity with magnetic fluid - Chekhun, V.F.; Yurchenko, O.V.; Naleskina, L.A.; Demash, D.V.; Lukianova, N.Yu.; Lozovska, Yu.V. (Experimental Oncology, 2013)
Aim: To study cytotoxicity of cisplatin conjugated with magnetic fluid (nanocomposite) upon exposure to magnetic field on sensitive and resistant to cisplatin MCF-7 human breast cancer cells. Methods: Cytotoxic activity was evaluated by MTT-test, intracellular iron accumulation was analyzed cytochemically, genotoxicity was studied by micronucleus test and DNA comet assay, ultrastructure was studied by electron microscopy techniques. Results: Nanocomposite of cisplatin was more toxic to MCF-7/S and MCF-7/CP cells compared to cisplatin in conventional pharmaceutical form. In nanocomposite-treated cells we observed more expressed signs of dystrophy (especially following application of magnetic field) and drastic alterations of nuclei ultrastructure with significant accumulation of iron nanoparticle clusters. The potent toxic action of nanocomposite is confirmed by electron microscopy and by marked genotoxicity, especially against MCF-7/CP cells. Conclusion: The enhancement of cyto- and genotoxicity of cisplatin nanocomposite combined with magnetic field in comparison with effect of convetntional cisplatin alone was demonstrated.